2017
DOI: 10.1071/rdv29n1ab189
|View full text |Cite
|
Sign up to set email alerts
|

189 EFFECT OF THE OVARIAN STIMULATION OF ANESTROUS CATS WITH eCG ON MORPHOLOGICAL QUALITY AND GENE EXPRESSION PROFILE OF CUMULUS-OOCYTE COMPLEXES

Abstract: The objective of this research was to evaluate the effect of eCG on morphological quality and gene expression profile of cumulus-oocyte complexes (COC) recovered from anestrous cats. For this purpose, 3 experimental groups were made. Group 1 consisted of 11 oestrous cats (oestrous); Group 2 had 13 anestrous cats (anestrous); and Group 3 was made up of 11 anestrous cats treated with a single subcutaneous dose of 200 IU of eCG. In oestrous and anestrous groups the ovaries were obtained directly by ovariohysterec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The eCG treatment increased the relative expression of gonadotrophin receptors (FSHR and LHCGR) and gonadotrophin-induced genes (EGFR, EGR1 and ESR2) in the COCs, which might be related to an enhanced oocyte competence [31]. Subsequently, we observed that the oocytes recovered from cats treated with eCG had an enhanced developmental capacity after parthenogenetic activation, which was reflected in a higher blastocyst rate compared to the control untreated group (32.8 and 16.9%, respectively) [unpublished data].…”
Section: In Vitro Fertilization In the Domestic Catmentioning
confidence: 99%
“…The eCG treatment increased the relative expression of gonadotrophin receptors (FSHR and LHCGR) and gonadotrophin-induced genes (EGFR, EGR1 and ESR2) in the COCs, which might be related to an enhanced oocyte competence [31]. Subsequently, we observed that the oocytes recovered from cats treated with eCG had an enhanced developmental capacity after parthenogenetic activation, which was reflected in a higher blastocyst rate compared to the control untreated group (32.8 and 16.9%, respectively) [unpublished data].…”
Section: In Vitro Fertilization In the Domestic Catmentioning
confidence: 99%